DETECTION OF METALLO Β-LACTAMASE ENZYME IN SOME GRAM NEGATIVE BACTERIA ISOLATED FROM BURN PATIENTS IN SULAIMANI CITY, IRAQ - Anoar, Khanda Abdulateef; Abodi Ali, Fattma; Ali Omer, Sherko (European Scientific Journal, ESJ, 2014)
Background: Metallo β-lactamase has emerged worldwide as powerful resistance determinants in Gram-negative bacteria. They hydrolyze virtually all classes of β-lactams except Monobactam, including Carbapenems, which often represent the last option for the treatment of infections with multidrug resistant Gram-negative bacteria. Objective: the aim of this study was to screen for genes coding for metallo β-lactamase such as, blaVIM, blaIMP and bla NDM among infected burn wound patients in Sulaimani city /Iraq. Methods: This prospective study was carried out in the Burn and Plastic Surgery Hospital in Sulaimani city at a period from April - October 2011. Genes responsible for metallo β-lactamase enzyme such as blaVIM, blaIMP and bla NDM were targeted to be screened by multiplex PCR mixture reaction among 177 Gram negative bacteria isolated from 230 burn patients. Results: One hundred seventy seven Gram negative bacteria were isolated and identified from infected burn wound. Out of 177 Gram negative bacteria isolated 46(25.9%) isolates were positive for different MBL genes by PCR. Conclusion : Common causes of multidrug resistant isolates among hospitalized burn patients in burn units was metallo β-lactamase which were not previously established in this hospital .